2002
DOI: 10.1603/0022-0493-95.3.640
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Spinosad on Four Classes of Wheat Against Five Stored-Product Insects

Abstract: Spinosad is a commercial reduced-risk pesticide that is naturally derived. Spinosad's performance was evaluated on four classes of wheat (hard red winter, hard red spring, soft red winter, and durum wheats) against adults of the lesser grain borer, Rhyzopertha dominica (F.); rice weevil, Sitophilus oryzae (L.); sawtoothed grain beetle, Oryzaephilus surinamensis (L.); red flour beetle, Tribolium castaneum (Herbst); and larvae of the Indianmeal moth, Plodia interpunctella (Hübner). Beetle adults (25) or P. inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
94
0
14

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(118 citation statements)
references
References 23 publications
10
94
0
14
Order By: Relevance
“…Before this, spinosad has already been proved very effective against a range of stored-grain insect species, even at lower rates than the application rate, in both laboratory (Fang et al 2002a, Toews and Subramanyam 2003, Nayak et al 2005, Daglish and Nayak 2006 and Þeld tests (Maier et al 2006, Subramanyam et al 2007, Daglish et al 2008. Due to the above-mentioned characteristics and its low mammalian toxicity, spinosad is a desirable alternative to the use of traditional grain protectants, especially organophosphorous insecticides (OPs), which often are very toxic to mammals.…”
mentioning
confidence: 99%
“…Before this, spinosad has already been proved very effective against a range of stored-grain insect species, even at lower rates than the application rate, in both laboratory (Fang et al 2002a, Toews and Subramanyam 2003, Nayak et al 2005, Daglish and Nayak 2006 and Þeld tests (Maier et al 2006, Subramanyam et al 2007, Daglish et al 2008. Due to the above-mentioned characteristics and its low mammalian toxicity, spinosad is a desirable alternative to the use of traditional grain protectants, especially organophosphorous insecticides (OPs), which often are very toxic to mammals.…”
mentioning
confidence: 99%
“…Some earlier studies (Subramanyam et al, 1999;Fang et al, 2002;Nayak et al, 2005) have shown that T. castaneum is the least susceptible stored-product pest to spinosad and that the recommended dose of 1 mg/kg cannot control adults of this species. After a 14-day exposure period, Subramanyam et al (1999) recorded a mortality of 52% among T. castaneum adults on wheat treated with spinosad at the dose of 6 mg/kg, and Fang et al (2002) reported that a full control of T. castaneum adults required spinosad doses exceeding 4 mg/kg, while Huang and Subramanyam (2007) found a 98% efficacy of spinosad at 2 mg/ kg after 12 days of contact of T. castaneum adults.…”
Section: Discussionmentioning
confidence: 99%
“…After a 14-day exposure period, Subramanyam et al (1999) recorded a mortality of 52% among T. castaneum adults on wheat treated with spinosad at the dose of 6 mg/kg, and Fang et al (2002) reported that a full control of T. castaneum adults required spinosad doses exceeding 4 mg/kg, while Huang and Subramanyam (2007) found a 98% efficacy of spinosad at 2 mg/ kg after 12 days of contact of T. castaneum adults. In those studies, spinosad applied to wheat at the dose of 5 mg/kg reached 97% efficacy only against adults of laboratory populations of T. castaneum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fang et al (2002) studied that spinosad is a feasible reduced-risk pesticide that is naturally derived. The spinosad against R. dominica and P. interpunctella and T, castaneum was proved very effective.…”
Section: Discussionmentioning
confidence: 99%